2006
DOI: 10.1136/bjo.2006.106005
|View full text |Cite
|
Sign up to set email alerts
|

Serious complications of local anaesthesia for cataract surgery: a 1 year national survey in the United Kingdom

Abstract: This large survey found a lower rate of reported serious complications with sub-Tenon's, topical and topical-intracameral LA compared with retrobulbar and peribulbar techniques. These "newer" methods may be preferable for routine cataract surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
124
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 146 publications
(133 citation statements)
references
References 18 publications
(10 reference statements)
4
124
0
5
Order By: Relevance
“…A 2003 postal survey of all UK consultants indicated that 96% of cataract surgery was carried out using LA, comprising 34% sharp needle, 43% subtenons, and 21% topical/intracameral. 4 The present study similarly found that almost 96% of cataract surgery was performed under LA, but with lower rates of sharp needle (19.5%) and higher rates of subtenons (46.9%) and topical/intracameral (27%) techniques. The authors consider that the most likely explanation for the difference between this study and the 2003 survey is a continued trend away from sharp needle techniques, as 86% of data in this study were collected between January 2004 and July 2006.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…A 2003 postal survey of all UK consultants indicated that 96% of cataract surgery was carried out using LA, comprising 34% sharp needle, 43% subtenons, and 21% topical/intracameral. 4 The present study similarly found that almost 96% of cataract surgery was performed under LA, but with lower rates of sharp needle (19.5%) and higher rates of subtenons (46.9%) and topical/intracameral (27%) techniques. The authors consider that the most likely explanation for the difference between this study and the 2003 survey is a continued trend away from sharp needle techniques, as 86% of data in this study were collected between January 2004 and July 2006.…”
Section: Discussionsupporting
confidence: 76%
“…The use of local anaesthetic techniques has risen from 46% in 1990 1 to 86% in 1997 3 and 96% in 2003. 4 There have also been major changes in the local anaesthetic techniques used, with peribulbar and retrobulbar being used in 65.6 and 16.9% of cases, respectively, in the 1996 5 survey, falling to 30.6-47.7 and 0.8-3.5%, respectively, in 2003; 4,6 subtenons anaesthesia increasing from 6.7 to 16.8-42.6% and topical anaesthesia increasing from 2.9 to 9.9-33.3% over the same time period. [4][5][6] The use of sedation with local anaesthesia (LA) has fallen from 6% in 1996 5 to 3.9% in 2003.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations